Accessibility to Health Care Services of Upazila Health Complex: Experience of Rural People: Accessibility to UHC services - Islam, Md Ziaul; Zaman, Farhana; Farjana, Sharmin; Khanam, Sharmin (Journal of Preventive and Social Medicine, 2020)
Background: Upazila health complex (UHC) is the first referral health facility at primary level of health care delivery system in the country. Rural people attend the UHCs to meet their health care needs and demands. But accessibility of the rural people to the UHCs is still not up to the mark. Objective: This study was conducted to assess accessibility of rural people to health care services of UHC. Methods: The study was a cross-sectional study, which was conducted at the Kaliakair UHC of Gazipur district in Bangladesh during the period from January to December 2016. The study included 300 rural adults, who were selected systemically. Data were collected by face-to-face interview with the help of a semi-structured questionnaire. Prior to data collection, informed written consent was taken from each participant. Results: The study revealed that males (51.3%) and females (48.7%) were very close in proportion with mean age of 35.73(±11.74) years. More than three fourth (77.3%) were married and 31.3% had primary education while 28.7% were illiterate. One third was housewives; average family size was 5.43 (±2.54) and average monthly family income was Tk.13920 (±10290.75). Around half of the participants choose the UHC for effective treatment and due to close distance from their residence while one third for low cost treatment and free of cost treatment. Around half of them didn‟t find any display board at the UHC. More than three fourth (82.0%) regarded doctor‟s behavior as „Good‟ while behavior of supporting staff was regarded „Good‟ by 66.0% participants. About half of the participants went to the UHC by rickshaw and 32.0% on foot. Average waiting time was 23.99 (±15.07) minutes to get access to treatment. Off all, 62.0% got full course of prescribed drugs but majority (71.3%) didn‟t get access to advised laboratory facility. Most (82.7%) could not be admitted in the hospital due to insufficient bed (24.2%) and inadequate treatment facility (22.6%), manpower (62.8%) and drug supply. Overall accessibility to UHC was „good‟ (21.3%) followed by „average‟ (31.3%) and „poor‟ (47.3%). It was found that females (53.3%) had significantly (p<0.05) poor accessibility to the UHC services than their counterpart males (41.1%). On the contrary, young adults, elderly, illiterate and primary education groups had significantly (p<0.05) „poor‟ accessibility to UHC services. Higher education (42.9% Masters and 36.4% Graduates) group had significantly „good‟ accessibility. More than half (53.1%) of the service holders and majority (60.0%) of higher income (Tk.30001-50000) group had had „average‟ and „good‟ accessibility respectively, which is statistically significant (p<0.05). Barriers to accessibility included long waiting time (67.0%), inadequate drug supply (62.0%), limited laboratory facility (40.0%), inadequate manpower (37.9%) and poor cooperation of the staff (32.0%) and communication (18.4%). Conclusion: To improve accessibility of the rural people to the health care services of the UHC, associated problems must be overcome by effective measures and program interventions. JOPSOM 2019; 38(2): 30-37